assuming the 1/2 at the end of each parenthetical does mean 1/2 of the resulting expression, the equation can be rewritten as follows (for the sake of simplicity): (x - 9)/2 + 2 = (x - 2)/2
Solve for x as follows:
(x - 9)/2 + 2 = (x - 2)/2
x/2 - 9/2 + 2 = x/2 - 2/2
x/2 - 5/2 = x/2 - 1
x/2 - x/2 = 5/2 - 1
0 = 3/2
Because 0 does not equal 3/2, there is no solution.
2007-03-04 05:06:46
·
answer #1
·
answered by superguytim 3
·
0⤊
1⤋
You can use the carrot (^) to raise to a power. ...
No problem, so we have:
(x - 9)^1/2 + 2 = (x - 2)^1/2
Rearranging:
(x - 2)^1/2 - (x - 9)^1/2 = 2 (eqn 1)
The form is:
a - b = 2
Knowing that:
(a-b)(a+b) = a^2 - b^2
Multiply LHS of eqn 1 by unity, where unity is written:
[(x - 2)^1/2 + (x - 9)^1/2]/[(x - 2)^1/2 + (x - 9)^1/2]
We get:
[(x - 2) - (x - 9)]/[(x - 2)^1/2 + (x - 9)^1/2] = 2
Or:
7/[(x - 2)^1/2 + (x - 9)^1/2] = 2 (eqn 2.)
Let:
a = (x - 2)^1/2
b = (x - 9)^1/2
From eqn.1:
a - b = 2
From eqn. 2:
7/[a + b] = 2
Or:
a + b = 3.5
Two eqns and two unknowns:
b = .75 = (x - 9)^1/2
a = 2.75 = (x - 2)^1/2
Only one of the above is needed to solve for x:
x = 9.5625
Fun in the sun!
2007-03-04 08:57:40
·
answer #2
·
answered by RWPOW 2
·
0⤊
1⤋
if :
1/2(x-9)+2=1/2(x-2)then :we multiply by 2 then we got :
(x-9)+4=(x-2)
x-9+4=x-2
x-5=x-2)
x-x=5-2
0=3
this equation is impossible
2007-03-04 05:15:59
·
answer #3
·
answered by hero yoy 1
·
0⤊
1⤋
x/2 - 9/2 + 2 = x/2 - 2/2
mmc = 2
x/2 - 9/2 + 4 = x/2 - 1
x/2 - x/2 = -1 + 9/2 -4
There is no value for X.
<>
2007-03-04 05:23:19
·
answer #4
·
answered by aeiou 7
·
0⤊
1⤋
1/2x -4+2=1/2x-1
multiply by common denominator
x-8+2=x-2
x-x=8-2
no solution
2007-03-04 05:08:33
·
answer #5
·
answered by Half-pint 5
·
0⤊
1⤋